pH-sensitive charge-conversion cinnamaldehyde polymeric prodrug micelles for effective targeted chemotherapy of osteosarcoma in vitro - Deng, Jiapeng; Liu, Su; Li, Guoqing; Zheng, Yien; Zhang, Weifei; Lin, Jianjing; Yu, Fei; Weng, Jian; Liu, Peng; Zeng, Hui (Frontiers in Chemistry, 2023)
Introduction: Chemotherapy is a common strategy for the treatment of osteosarcoma. However, its therapeutic efficacy is not ideal due to the low targeting, lowbioavailability, and high toxicity of chemotherapy drugs. Nanoparticles can improve the residence time of drugs at tumor sites through targeted delivery. This new technology can reduce the risk to patients and improve survival rates. To achieve this goal, we developed a pHsensitive charge-conversion polymeric micelle [mPEG-b-P(C7-co-CA) micelles] for osteosarcoma-targeted delivery of cinnamaldehyde (CA). Methods: First, an amphiphilic cinnamaldehyde polymeric prodrug [mPEG-b-P(C7-co-CA)] was synthesized through Reversible Addition-Fragmentation Chain Transfer Polymerization (RAFT) polymerization and post-modification, and self-assembled into mPEG-b-P(C7-co-CA) micelles in an aqueous solution. The physical properties of mPEG-b-P(C7-co-CA) micelles, such as critical micelle concentration (CMC), size, appearance, and Zeta potential were characterized. The CA release curve of mPEG-b-P(C7-co-CA) micelles at pH 7.4, 6.5 and 4.0 was studied by dialysis method, then the targeting ability of mPEG-b-P(C7-co-CA) micelles to osteosarcoma 143B cells in acidic environment (pH 6.5) was explored by cellular uptakeassay. The antitumor effect of mPEG-b-P(C7-co-CA) micelles on 143B cells in vitro was studied by MTT method, and the level of reactive oxygen species (ROS) in 143B cells after mPEG-b-P(C7-co-CA) micelles treatment was detected. Finally, the effects of mPEG-b-P(C7-co-CA) micelles on the apoptosis of 143B cells were detected by flow cytometry and TUNEL assay. Results: An amphiphilic cinnamaldehyde polymeric prodrug [mPEG-b-P(C7-co-CA)] was successfully synthesized and self-assembled into spheric micelles with a diameter of 227 nm. The CMC value of mPEG-b-P(C7-co-CA) micelles was 25.2 mg/L, and it showed a pH dependent release behavior of CA. mPEG-b-P(C7-co-CA) micelles can achieve chargeconversion from a neutral to a positive charge with decreasing pHs. This charge-conversion property allows mPEG-b-P(C7-co-CA) micelles to achieve 143B cell targeting at pH 6.5. In addition, mPEG-b-P(C7-co-CA) micelles present high antitumor efficacy and intracellular ROS generation at pH 6.5 which can induce 143B cell apoptosis. Discussion: mPEG-b-P(C7-co-CA) micelles can achieve osteosarcoma targeting effectively and enhance the anti-osteosarcoma effect of cinnamaldehyde in vitro. This research provides a promising drug delivery system for clinical application and tumor treatment.